**6. If n (E) = 40, n (A) = 22, n (ANB) = 8 and n ((AUB)') = 6, determine n(B)**

**Answer:**

4

**Step-by-step explanation:**

First n(AUB)=n(E) - n((AUB)')

So n(AUB) = 40 - 6 = 34

Now all u hv to do is use the formulae,

n(AUB) = n(A) + n(B) - n(ANB)

So when u substitute above values,

34=22 + n(B) - 8

So,

n(B) = 4

Rate answer

If your question is not fully disclosed, then try using the search on the site and find other answers on the subject Mathematics.

Find another answersMathematics, published 11.05.2023

Mathematics, published 23.03.2023

Use the equation to identify the center and radius of the circle (X+3)^2+(y-7^2=11

Mathematics, published 27.05.2023